The Oxford Handbook of Eschatology - Walls, Jerry L. (New York Oxford University Press, 2010)
The Oxford Handbook of Eschatology provides an invaluable critical survey of this diverse body of thought and practice from a variety of perspectives: biblical, historical, theological, philosophical, and cultural. Through centuries of Christian thought
Keywords: Eschatology. Eschatologie